51‐5: Late-News Paper: Fast Motion Picture Response Color Filter LCOS for Wearable Applications. Issue 1 (30th May 2018) - Li, Yuet-Wing; Chen, Wen-Hsu; Lin, Chi-Wen; Fan-Chiang, Kuan-Hsu; Kuo, Hung-Chien; Tsai, Hsien-Chang
Abstract : The display for augmented reality (AR) applications has to update image promptly in order to cope with the user's head movement or any environment change. It makes image blur become noticeable if the motion picture response time of the AR display is longer than 1.5ms. We propose an image blur free Color Filter LCOS (CFLCOS) which equipped with 1.9ms liquid crystal response time; analog frame buffer and 480fps refreshing rate. It is found that the MPRT of such device can be as fast as <1.5ms.